Biography of a Painted Wessel from Starčevo: Discovering Layers of Meaning - Olga Bajčev (University of Belgrade, 2020)
Scientific interest in the painted pottery of the Starčevo culture in Serbia dates back to the very beginnings of research and the first works on the relative-chronological systematization of the Early and Middle Neolithic of the central Balkans. This paper presents the deconstruction of our established notion of painted ceramics as the ultimate parameter of relative-chronological dating, the most representative material reflection of the cultural identity of the people of Starčevo culture and the highest achievements of Starčevo culture. The paper discusses circumstances and archaeological practices through which this ingrained view and knowledge of painted pottery was formed. The research is based on the analysis of the biography of a painted vessel from the Starčevo-Grad site, having in mind that a detailed life history of an object can shed light on wider phenomena in the archaeological discipline. The aim of this paper is to remind that objects do not have a single essential meaning, but that their meaning shifts and builds through changes in the historical and social context, as well as through changes of actors gathered around certain practices in which the objects are used. The biography of the painted vessel is therefore viewed as a series of assemblages of relations in two planes, through which its identity and layers of meaning were built. The first plane is the Neolithic, in which the focus is on the practices of painting and use, and the second is her life in the role of an archaeological artifact, during which she moves from the sphere of scientific research and musealization to the sphere of negotiating contemporary cultural identities. By applying a new analytical approach, we discovered that this vessel was not very skilfully and carefully painted, and that as such it does not testify to the highest achievements of Starčevo culture, but to a social practice, learning, apprentices and mastering the skill of pottery painting. Therefore, I believe that by reducing painted pottery to relative-chronological parameters and luxury objects, we lose sight of the possibilities through which we can build much more diverse interpretations of the past.